2023
DOI: 10.1039/d2bm01959k
|View full text |Cite
|
Sign up to set email alerts
|

TCPP/MgO-loaded PLGA microspheres combining photodynamic antibacterial therapy with PBM-assisted fibroblast activation to treat periodontitis

Abstract: Bacteria eradication and subsequent periodontal tissue reconstruction are the major tasks for periodontitis treatment. Commonly used antibiotic therapy suffers from antibiotic resistance. Meanwhile, promoting fibroblasts activity is crucial for re-establishing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Multifunctional microspheres (PMT), using poly (lactic co-glycolic acid) (PLGA) to encapsulate a phenylporphyrin derivative, namely tetrakis (4-carboxyphenyl) porphyrin (TCPP), along with magnesium oxide (MgO) nanoparticles have also been produced and assessed for the treatment of periodontitis (Figure 11). PMT exhibited a dual function: an antibacterial photodynamic effect against periodontal pathogens (F. nucleatum and P. gingivalis) through the production of reactive oxygen species and a fibroblast activation effect, crucial for the reconstruction of damaged periodontal structures [70]. PMT enhanced viability, adhesion and activation of fibroblasts, as evidenced by increased gene expressions of fibronectin 1, Col1a1 and vinculin.…”
Section: Porphyrin-related Nanoparticles and Heme-albumin Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifunctional microspheres (PMT), using poly (lactic co-glycolic acid) (PLGA) to encapsulate a phenylporphyrin derivative, namely tetrakis (4-carboxyphenyl) porphyrin (TCPP), along with magnesium oxide (MgO) nanoparticles have also been produced and assessed for the treatment of periodontitis (Figure 11). PMT exhibited a dual function: an antibacterial photodynamic effect against periodontal pathogens (F. nucleatum and P. gingivalis) through the production of reactive oxygen species and a fibroblast activation effect, crucial for the reconstruction of damaged periodontal structures [70]. PMT enhanced viability, adhesion and activation of fibroblasts, as evidenced by increased gene expressions of fibronectin 1, Col1a1 and vinculin.…”
Section: Porphyrin-related Nanoparticles and Heme-albumin Complexesmentioning
confidence: 99%
“…Microcomputed tomography analysis and histological staining revealed reduced inflammatory cells, increased collagen production and higher alveolar bone levels in the PMT group. Therefore, PMT, with its combined photodynamic therapy (PDT) and photobiomodulation (PBM)assisted fibroblast activation modes, holds promise as an effective strategy by which to combat periodontitis and its inflammatory manifestations [70].…”
Section: Porphyrin-related Nanoparticles and Heme-albumin Complexesmentioning
confidence: 99%
“…Mechanically, the new antibacterial nanoparticles kill bacteria via a photodynamic effect that disrupts the bacterial structure and increases the permeability of the membrane. 12 Recently, broad antibacterial research interests have been diverted to the development of new methods for the interference of central metabolisms. 13 In Staphylococcus aureus (S. aureus), lipoproteins and tricarboxylic acid cycle regulate bacterial metabolism through pyruvate metabolic cycle, which is related to the change of glyoxylate and tricarboxylic acid, 14 since glyoxylate is found upregulated during bacterial infections or iron-limiting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al designed a photodynamic antimicrobial agent attenuating bacterial metabolite by employing poly­(lactic- co -glycolic acid) (PLGA) micro-spheres to TCPP and magnesium oxide (MgO) nanoparticles. Mechanically, the new antibacterial nanoparticles kill bacteria via a photodynamic effect that disrupts the bacterial structure and increases the permeability of the membrane . Recently, broad antibacterial research interests have been diverted to the development of new methods for the interference of central metabolisms .…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in chemical reactions, biochemical processes and organic pollutant treatment. [51][52][53][54][55][56][57] Xiao's group has demonstrated that 1 O 2 can efficiently seize a proton from the benzylic C-H bond of PS by hydrogen atom transfer (HAT), which produces benzyl radicals, further induces the oxidative degradation of PS, and finally obtains benzoic acid. 36 The critical role of 1 O 2 inspired us to consider whether the PPOPs can trigger the degradation of PS efficiently even in the air.…”
mentioning
confidence: 99%